Lippincott Illustrated Reviews : Pharmacology - Whalen, Karen L. (Lippincott illustrated reviews, 2023)
Lippincott® Illustrated Reviews: Pharmacology, 8th Edition, presents up-to-date drug information in an accessible format ideal for effective review. Part of the popular Lippincott® Illustrated Reviews series, this concise resource features clear writing and hundreds of illustrations that break down complex pharmacological information, so it is understandable and accessible. Sequential images present mechanisms of action and focus on showing rather than telling students how drugs work, and review questions with answers deliver powerful, practical exam preparation